Quantum soliton mass corrections in sl(n) affine Toda field theory - Timothy Hollowood (Physics Letters B, 1992)
The first quantum mass corrections for the solitons of complex $sl(n)$ affine Toda field theory are calculated. The corrections are real and preserve the classical mass ratios. The formalism also proves that the solitons are classically